Cardiovascular risk and bipolar disorder: factors associated with a positive coronary calcium score in patients with bipolar disorder type 1 - Wageck, Aline R. (Braz J Psychiatry, 2017)
OBJECTIVE: Cardiovascular disease is the leading cause of death in patients with bipolar disorder. The aim of this study was to evaluate the factors associated with positive coronary calcium score (CCS) in individuals with bipolar disorder type 1. METHODS: Patients from the Bipolar Disorder Program at Hospital de Clínicas de Porto Alegre, Brazil, underwent computed tomography scanning for calcium score measurement. Clinical and sociodemographic variables were compared between patients according to their CCS status: negative (CCS = 0) or positive (CCS > 0). Poisson regression analysis was used to examine the association of CCS with number of psychiatric hospitalizations. RESULTS: Out of 41 patients evaluated, only 10 had a positive CCS. Individuals in the CCS-positive group were older (55.2±4.2 vs. 43.1±10.0 years; p = 0.001) and had more psychiatric hospitalizations (4.7±3.0 vs. 2.6±2.5; p = 0.04) when compared with CCS- negative subjects. The number of previous psychiatric hospitalizations correlated positively with CCS (p < 0.001). CONCLUSION: Age and number of psychiatric hospitalizations were significantly associated with higher CCS, which might be a potential method for diagnosis and stratification of cardiovascular disease in bipolar patients. There is a need for increased awareness of risk assessment in this population.